DEVELOPMENT OF TECHNOLOGY FOR OBTAINING INTEGRATED FERTILIZER FROM SOLID WASTE OF PRODUCTION: ӨНДІРІСТІҢ ҚАТТЫ ҚАЛДЫҚТАРЫНАН КЕШЕНДІ ТЫҢАЙТҚЫШТАР АЛУ ТЕХНОЛОГИЯСЫН ӘЗІРЛЕУ - Kozhakhmetova, Aidana (Academic Journal of Physical and Chemical Sciences, 2022)
The article presents the results of chemical analyzes of carbonate-siliceous dolomitized phosphate raw materials from the Aksai deposit and the components of the charge to obtain a new environmentally safe nomenclature of fertilizer mixture. In order to improve soil properties and increase and fertility, a developed technological scheme is proposed based on the results of the studies carried out, a basic technological scheme for obtaining a fertilizer mixture based on solid waste from various industries has been developed. As a component of the charge, enriched and fired vermiculite is used at a temperature of 850-950℃ in order to increase the porosity of the material that retains soil moisture. As an additive containing humates and trace elements, internal overburden and screenings of fines formed during coal mining can serve. The simplicity of the hardware design of the technological process for obtaining such fertilizer mixtures makes it possible to switch to the preparation of new, non-traditional brands of mineral fertilizers. The main purpose of this article is to develop a technology for restoring saline soils that have lost their fertility by adding a mixture of slag formed during solid waste incineration, it is possible to obtain an organo-mineral complex fertilizer enriched with macro- and microelements.